2019
DOI: 10.1002/jcp.29134
|View full text |Cite
|
Sign up to set email alerts
|

TGF‐β/SMAD4 signaling pathway activates the HAS2–HA system to regulate granulosa cell state

Abstract: Both TGF-β/SMAD4 signaling pathway and HAS2-HA system have been shown to control granulosa cell (GC) state in mammalian ovary. However, the regulatory relationship between TGF-β/SMAD4 signaling pathway and HA system in GCs is not well known. Here, we report that the TGF-β/SMAD4 signaling pathway activates the HAS2-HA system by binding directly to the HAS2 promoter, ultimately controlling the GC state via the CD44-Caspase3 axis. SMAD4-induced HAS2 expression, HAS2-driven HA secretion, and HAS2-mediated GC state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…Furthermore, SMAD4 generally functions as a transcription factor, directly acting on the key genes including the miRNAs of important events in the female reproductive cycle [ 46 ]. For example, the key genes HAS2 , for inducing ovulation [ 47 ], and ALK3 , for maintaining embryo implantation [ 48 ], are all transcriptional targets of SMAD4. Recently, several miRNAs involved in critical events in the female reproductive cycle, such as miR-29c, for influencing the follicular development fate [ 12 ], have also been shown to be directly regulated by the transcription factor SMAD4.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, SMAD4 generally functions as a transcription factor, directly acting on the key genes including the miRNAs of important events in the female reproductive cycle [ 46 ]. For example, the key genes HAS2 , for inducing ovulation [ 47 ], and ALK3 , for maintaining embryo implantation [ 48 ], are all transcriptional targets of SMAD4. Recently, several miRNAs involved in critical events in the female reproductive cycle, such as miR-29c, for influencing the follicular development fate [ 12 ], have also been shown to be directly regulated by the transcription factor SMAD4.…”
Section: Discussionmentioning
confidence: 99%
“…Estradiol can stimulate HAS2 mRNA expression when combined with insulin-like growth factor-1, insulin, and follicle-stimulating hormone ( Chavoshinejad et al ., 2016 ). The TGF-β/Smad4 signaling pathway can activate the HAS2-HA system ( Li et al ., 2020 ). In the mammalian ovary, epigenetic factor microRNA-574 directly inhibits HAS2 expression and subsequently improves oocyte maturation ( Pan et al ., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…SMAD4 is the most studied miRNA target gene among those in the ovarian BMP/Smad signaling pathway. miR-224 (Yao et al, 2010), miR-144 (Zhou et al, 2017, and miR-26b (Li et al, 2019) can regulate ovarian function by targeting SMAD4. In this study, we showed that miR-1306 direct targets BMPR1B gene in the ovine granulosa cells.…”
Section: Discussionmentioning
confidence: 99%